The Urgency of Organizing Insurtech in Improving Insurance Services Based on POJK No. 13/POJK.02/2018 Regarding Digital Financial Innovation in the Financial Services Sector - Rindia Fanny Kusumaningtyas; Ristina Yudhanti; Afifah Widyastuti (Universitas Negeri Semarang, 2023)
The business sector needs to invest in building information technology architecture to leverage tools and services offered by digital transformation, one of which is the insurance sector with its Insurtech. The presence of Insurtech with its digital services is expected to drive increased financial inclusion in the insurance sector by reaching the public through fast and limitless services. Behind the opportunities presented by the Insurtech industry, there are challenges to be faced. The research problem in this study is how the implementation of customer data protection in the implementation of Insurtech based on Financial Services Authority Regulation No. 13/POJK.02/2018 on Digital Financial Innovation in the Financial Services Sector. The purpose of this research is to analyze and explain how the implementation of customer data protection in the implementation of Insurtech based on Financial Services Authority Regulation No. 13/POJK.02/2018 on Digital Financial Innovation in the Financial Services Sector. The research method used in this study is a qualitative research method, using a socio-legal approach. The results of the study show the urgency of Insurtech based on Financial Services Authority Regulation No. 13/POJK.02/2018 involving the analysis of regulations and interviews with PT Prudential Life Assurance, PT Jasa Raharja, BPJS Kesehatan, and PT Asuransi Jiwa Inhealth Indonesia. The results include the implementation of customer data protection, BPJS Kesehatan's service innovations, PT Jasa Raharja's role in accident insurance claims, and the digital transformation of PT Asuransi Jiwa Inhealth Indonesia through the FitAja application.